A fast spectrofluorimetric method for determination of carbinoxamine maleate in the nano-molar range. Application to pharmaceutical preparations, biological fluids and stability studies. Issue 31 (31st July 2018) - Aly, Fatma Ahmed; EL-Enany, Nahed; Elmansi, Heba; Nabil, Amany
Abstract : Carbinoxamine maleate (CBX), which is a common ingredient of cold and cough treatment preparations, is determined by a sensitive, simple and convenient spectrofluorimetric method in its pure form, pharmaceutical preparations and spiked human plasma. Abstract : Carbinoxamine maleate (CBX), which is a common ingredient of cold and cough treatment preparations, is determined by a sensitive, simple and convenient spectrofluorimetric method in its pure form, pharmaceutical preparations and spiked human plasma. This method relies on measuring the native fluorescence intensity of CBX in methanol at a wavelength of 273/308 nm. Furthermore, it was utilized for stability investigation of CBX under stress conditions guided by the International Conference of Harmonization (ICH). Until now, no fluorescence-based method has been reported for CBX, despite the advantages of this technique. Therefore, we investigated in this study, for the first time, the CBX fluorescence behavior to suggest a new spectrofluorimetric method which offers the advantages of simplicity and sensitivity over previously published reports. The proposed method has a limit of detection of 0.66 ng mL −1 and a limit of quantitation of 1.99 ng mL −1, which permits its use in the determination of CBX in spiked human plasma samples as a fast and cost-effective tool for in vitro investigation with satisfactory results. The method was validated in terms of linearity, accuracy, precision, and robustness and the results showed a non-significant difference in accuracy and precision, relative to the spectrophotometric comparison method.